Reading India : selections from economic and political weekly (Orient blackswan, 2019)
Book Description Orient Blackswan, 2019. Soft cover. Condition: New. 1st Edition. Contents: I. Early Village Studies: 1. The Social Structure of a Mysore Village/M. N. Srinivas. 2. Social Structure and Change in a UP Village/McKim Marriott. 3. An Oriya Hill Village/F. G. Bailey. II. Rural Structures: 4. The Myth of Self-Sufficiency of the Indian Village/M. N. Srinivas and A. M. Shah. 5. Chamar Family in a North Indian Village: A Structural Contingent/Bernard S. Cohn. 6. Individual Case Study and the Statistical Method in Social Investigation/Iravati Karve. III. Identity and Politics: 7. The RSS/D. V. Kelkar. 8. Sripuram: A Village in Tanjore District/Andre Beteille. 9. Caste Orientation of Political Factions: Modasa Constituency: A Case Study/Rajni Kothari and Ghanshyam Shah. 10. Class and Caste/Nirmal Kumar Bose. IV. Analytical Frameworks: 11. Keynesian Economics and Underdeveloped Countries/A. K. Dasgupta. 12. Teaching Economics/Joan Robinson. 13. Peasant Economy as a Category in Economic History/Daniel Thorner. V. Development and Planning: 14. A Case of Aborted Growth: India, 1860 1900: Some Suggestions for Research/George Rosen. 15. How to Industralise an Underdeveloped Area/Paul N. Rosenstein-Rodan. 16. Choice Elements in Intertemporal Planning/S. Chakravarti and R. S. Ekaus. 17. Structural Linkages in the Indian Economy/Krishna K. Bharadwaj. 18. Relative Rates of Growth: Agriculture and Industry/Ashok Rudra. VI. Policy Debates: Agriculture: 19. The Shifting Fortunes of Agriculture: The General Setting/W. Arthur Lewis. 20. Retrospect: The Shifting Fortunes of Agriculture: The Experience of Less Fully Developed Countries/D. R. Gadgil. 21. A Note on Cooperative Farming/Amlan Datta. 22. Context for Cooperatives in Rural India/Daniel Thorner. 23. Agrarian Structure in Twelve Districts/M. L. Dantwala. 24. Major and Minor Irrigation Works: A Preliminary Comparison of Costs and Returns/Ranjit Gupta. 25. Size of Holdings and Productivity/Amartya Kumar Sen. 26. Problems of Numbers in Cattle Development/V. M. Dandekar. 27. The Marketable Surplus Function for a Subsistence Crop: An Analysis with Indian Data/Raj Krishna. VII. Policy Debates: Industry: 28. Small-scale Industries: Problem of Technological Change/K. N. Raj. 29. Mill versus Cottage Industries: A Method of Appraisal/Jan Tinbergen. 30. Size, Technology and Economics: A Study of the Indian Cotton Textiles Industry/J. C. Sandesara. VIII. Public Finance and Distribution: 31. Federal Finance Perspectives/Bhabatosh Datta. 32. Tax Reform in India/Nicholas Kaldor. 33. Economic Growth and Rural-Urban Income 327 Distribution: 1950 51 to 1960 61/V. K. R. V. Rao. 34. Distribution of Public Health and Education Services/N. Bhattacharya and B. Dey. IX. Culture, Administration and Leadership: 35. Man and Plan in India: The Background/D. P. Mukerji. 36. The Language Problem: A Solution/O. L. Chavarria-Aguilar. 37. English, Hindi and the Regional Languages/I. P. Desai. 38. Administrative Institutions of Government/Rajni Kothari. 39. Generalists versus Specialists in Indian Administration I/Asoke Mohan Roy. 40. Generalists versus Specialists in Indian Administration II/Asoke Mohan Roy. 41. Generalists versus Specialists in Indian Administration: A Comment/Deepak Lal. 42. The Meaning of Jawaharlal Nehru/Rajni Kothari. 43. Economic Ideology of Jawaharlal Nehru/M. L. Dantwala. The Economic Weekly was launched in 1949, shortly after Indian Independence. This period was full of hope and expectation, but also questioning and rethinking. Under the leadership of its illustrious founding editor, Sachin Chaudhuri, the journal soon became a major platform for the finest minds of the time, providing a diverse range of scholarship and space for differing, often conflicting, ideological positions. Reading India: Selections from The Economic Weekly: Volume 1: 1949 1965 brings together landmark studies in sociology, politics and economics that capture the major analytical and policy debates published in the journal from 1949 65.The articles span a wide range of studies, exploring. Seller Inventory # 131611